An investigation into the impact of Culturally Sustaining Pedagogy (CSP) on students’ learning and the teacher’s practice in an adult English Second Language (ESL) presentation skills classroom - Ponnen, Michelle (My University, 2020)
This study seeks to contribute to the field of second language instruction by investigating the impact of Culturally Sustaining Pedagogy (CSP) on students’ learning and the teacher in an adult English second language Presentation Skills classroom. The study aimed to discover the impact of CSP strategies on adult ESL students’ learning of Presentation Skills, the affordances and limitations of CSP strategies for adult ESL students’ learning of Presentation Skills as well as to ascertain the teacher’s reflections about the effectiveness of the Presentation Skills course with the use of CSP strategies. The study was conducted at a language school in Johannesburg with seven second language learners who were enrolled for a ten week English short course on Presentation Skills. They came from a wide range of linguistic, cultural, economic and social backgrounds and were between the ages of 29 to 60 years old. Data was collected using a questionnaire, a teacher’s journal and the students’ reflective paragraphs.
A research report submitted in fulfilment of the requirements for the degree of Master of Education in Applied Language and Literacy Education to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020